VALIDATION OF CREATIVE AND INNOVATIVE CONTENT-BASED NAHWU MEDIA AND MATERIALS ON SOCIAL MEDIA INSTAGRAM - Lailil Maulidiyah; Sulaikho, Siti; Suparmanto (Lughatu Ad-Dhat, 2024)
Instagram is one of the most popular social media platforms, particularly among the Gen Z demographic. A lot of individuals use Instagram to share content, including their daily routines, food reviews, and educational material. In Arabic, nahwu can be synonymous with grammar. Many students still struggle with understanding nahwu and as a result, they are not able to become proficient in learning Arabic. As a result, scholars develop educational materials as unique and inventive nahwu content on the Instagram social media platform. The purpose of this study is to assess whether it is possible to create creative and innovative content-based materials on nahwu for Instagram social media. The participants in this research were twenty students from class XII IPA 1 at MA Al-Bairuny Sambongdukuh Jombang. This research falls under the category of descriptive quantitative. Once the nahwu learning media has been developed, approved, and replicated, and after undergoing various revisions, it is now ready to be utilized for learning nahwu on Instagram. Data was gathered through the use of a survey. Material and media experts evaluated the validation questionnaire. The evaluation employs a Likert scale featuring options like very feasible, feasible, quite feasible, and less feasible. Material experts have yielded a validation result of 92.4%, falling into the very feasible category. Similarly, media experts have rated the validation assessment at 96.7%, also within the very feasible category.